2013
DOI: 10.1136/bmjquality.u632.w640
|View full text |Cite
|
Sign up to set email alerts
|

Cardiovascular health monitoring in patients with psychotic illnesses: A project to investigate and improve performance in primary and secondary care

Abstract: Patients with psychotic illnesses are predicted to die 15 years younger than the national average. The chief cause is cardiovascular disease (1). Evidence-based guidelines including those produced by the National Institute of Health and clinical Excellence and the Quality Outcomes Framework, recommend regular monitoring of their cardiovascular risk (2,3,4).Primary health care audits were undertaken in an urban and a rural setting. These looked at the proportion of patients who had their physical health regular… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2014
2014
2017
2017

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 6 publications
0
4
0
Order By: Relevance
“…People with SMI are less likely to receive cardiovascular disease (CVD) screening, compared with people with diabetes, 9 and CVD checks are not always performed in accordance with national guidance. 10 …”
Section: Introductionmentioning
confidence: 99%
“…People with SMI are less likely to receive cardiovascular disease (CVD) screening, compared with people with diabetes, 9 and CVD checks are not always performed in accordance with national guidance. 10 …”
Section: Introductionmentioning
confidence: 99%
“…Other published studies indicate pharmacy checks on monitoring prior to dispensing the medication 32 and combined projects between primary and secondary care 33 can be effective.…”
Section: Designmentioning
confidence: 99%
“…Repeated studies have demonstrated that the lifespan of people with severe mental illness (SMI) is shorter compared to the general population, equating to a [13][14][15][16][17][18][19][20][21][22][23][24][25][26][27][28][29][30] year shortening in life span, mostly due to physical illness. 6 Many physical disorders such as cardiometabolic and nutritional, have been identified as being more prevalent in individuals with serious mental illness compared to the general population.…”
Section: Introductionmentioning
confidence: 99%
“…Some teams have relied on psychiatric doctors' input and struggled to produce sustained improvements. 14 Common barriers to management of physical illness in patients with severe mental illness are poor engagement and lack of training of mental health professionals. 15 Some suggestions to improve care include using algorithms and monitoring tools, educating and training staff, and bridging the gap between physical and mental health to promote a policy of coordinated and integrated health care for persons with serious mental illness.…”
Section: Introductionmentioning
confidence: 99%